The Role of Ramadan Fasting Values For Character Education of Elementary School Students - Kuswara Kuswara; Yena Sumayana (ADI Publisher, 2020)
This article aims to study the values contained in fasting education for elementary school students. The values of education are the value of religious education, the value of moral education, social education, and cultural education values. Fasting is a religious activity that people Islam as a form of obedience to His God in addition to other services. Ramadan fasting is a refrain from eating, drinking, and having sex and other things that make it clear that fasting will not rise from dawn until sunset during Ramadan. The current phenomenon is increasingly reduced worship activities, tepo seliro, gotong royong, mutual help, and attitudes other positive attitudes such as honesty, discipline, responsibility, and tolerant living in life. Ramadan fasting not only emphasizes refraining from eating and drinking only, but training in improving faith, mental coaching, morality, and understanding the meaning of difference. In elementary school, these grades need to be instilled as a cornerstone of students in their development, especially in the aspects of personality such as: character, behavior, responsibility, discipline, and social spirit.